Strategi Pengembangan Potensi Wisata Alam di Desa Abangsongan, Kintamani, Kabupaten Bangli, Bali - Tyas Raharjeng Pamularsih (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2020)
The Kintamani area is very famous for natural tourist destinations such as Lake Batur and Mount Batur. However, it turns out that Kintamani has several other natural tourism potentials that are not yet known by tourists, such as Mount Abang in Abangsongan Village. This village has potential in the tourism sector which is very potential, including the lake which is used as water tourism, forest tourism, Mount Abang which has not been optimally developed. The purpose of this research is to identify the tourism potential in Abangsongan Village and find out a suitable development strategy using the SWOT analysis technique. The data used by the author is in the form of qualitative data collected through direct observation and interviews. The data obtained in the field will be analyzed using qualitative descriptive analysis techniques by describing the situation in the field. In addition, there is also a need for a study of the potential and appropriate policies in realizing Abangsongan Village into a tourist destination. Based on the results of the SWOT analysis, the tourism development strategy in Abangsongan Village that may be implemented is as follows: Promotion and publication through the creation of tour packages, construction of trekking routes and outbound facilities, training and counseling on environmental conservation, coordination of protection of tourist areas, periodic evaluation and monitoring of impacts tourism, Collaboration and cooperation with investors regarding the development and management of existing natural tourism potential, Empowerment of communities around tourist areas in Abangsongan Village especially around Lake Batur and Mount Abang, Making management plans and stabilizing tourism areas in Abangsongan Village, Training in tourism such astraining guiding tour, homestay management andtraining culinary.Keywords: Tourism Potential, Development, Strategy, SWOT. AbstrakKawasan Kintamani sangat terkenal dengan destinasi wisata alam seperti Danau Batur dan Gunung Batur. Namun, ternyata di Kintamani memiliki beberapa potensi wisata alam lainnya yang belum diketahui wisatawan seperti Gunung Abang yang ada di Desa Abangsongan. Desa ini memiliki potensi dalam bidang pariwisata yang sangat potensial di antaranya danau yang digunakan sebagai wisata air, hutan wisata, Gunung Abang yang belum secara optimal dikembangkan. Tujuan dari penelitian ini adalah untuk mengidentifikasi potensi wisata yang ada di Desa Abangsongan dan mengetahui strategi pengembangan yang cocok dengan menggunakan teknik analisis SWOT. Data yang digunakan oleh penulis berupa data kualitatif yang dikumpulkan melalui observasi langsung dan wawancara. Data yang didapat di lapangan akan dianalisis menggunakan teknik analisis deskriptif kualitatif dengan menggambarkan situasi yang ada di lapangan. Selain itu, juga perlu adanya kajian mengenai potensi dan kebijakan yang sesuai dalam merealisasikan Desa Abangsongan menjadi suatu destinasi wisata. Berdasarkan hasil analisis SWOT maka strategi pengembangan wisata Desa Abangsongan yamg mungkin dapat diterapkan sebagai berikut : Promosi dan publikasi melalui pembuatan paket wisata, Pembangunan jalur trekking dan sarana outbond, Pelatihan dan penyuluhan konservasi lingkungan, Koordinasi perlindungan kawasan wisata, Evaluasi dan monitoring secara berkala mengenai dampak pariwisata, Kolaborasi dan kerja sama dengan investor mengenai pengembangan dan pengelolaan potensi wisata alam yang ada, Pemberdayaan masyarakat sekitar kawasan wisata di Desa Abangsongan khusunya sekitar Danau Batur dan Gunung Abang, Pembuatan rencana pengelolaan dan pemantapan kawasan wisata di Desa Abangsongan, Pelatihan dalam bidang kepariwisataan seperti pelatihan tour guiding, pengelolaan homestay dan pelatihan culinary.Kata Kunci: Potensi Wisata, Pengembangan, Strategi, SWOT .